Efficacy of different nasal irrigation treatments versus placebo in allergic rhinitis: a systematic review and network meta-analysis - Hu, Qidi; Kong, Lili; Zhou, Yi; Shen, Wen; Sun, Yao; Deng, Jing (Frontiers in Pharmacology, 2025)
PurposeAllergic rhinitis (AR) is a globally prevalent disease, and nasal irrigation is one of its effective treatments. This study aims to compare the efficacy and effectiveness of different nasal irrigation treatments on AR patients’ nasal symptoms and quality of life (QoL).MethodsStudies on AR patients using different nasal irrigation treatments were searched from Cochrane, Embase, Pubmed, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Database, and China Biology Medicine disc (CBM) up to 29 March 2025. The quality of the included studies was independently assessed using the NIH quality evaluation tool. The primary outcomes included relevant scale scores from the Total Nasal Symptom Score (TNSS), and secondary outcomes included those from the Rhinoconjuctivitis Quality of Life Questionnaire (RQLQ). Random-effects or fixed-effects models were selected for network meta-analysis, and mean difference (MD) was calculated with a 95% credibility interval (CrI). Surface under the cumulative ranking curve (SUCRA) was employed to rank various interventions. R 4.4.1 was used for statistical analysis.Results23 studies involving 3,584 patients were identified. The results of the network meta-analysis showed that compared with the placebo, multiple nasal irrigating agents were more significantly efficacious and effective. In terms of alleviating nasal symptoms (a lower score indicated better effectiveness), resveratrol was the most efficacious [MD: −7.7, 95% CrI (−14.0, −1.1)] (SUCRA = 92.08%), and budesonide also showed significant efficacy and effectiveness [MD: −5.6, 95% CrI (−10.0, −0.99)] (SUCRA = 83.39%). In terms of improving QoL (a lower score indicated better efficacy), cinnamon bark was the most efficacious [MD: −1.3, 95% CrI (−1.6, −0.96)](SUCRA = 95.78%). In addition, hydrogen-rich water [MD: −1.2, 95% CrI (−2.4, 0.10)](SUCRA = 82.58%) and fluticasone [MD: −0.83, 95% CrI (−0.94, −0.71)](SUCRA = 81.49%) also showed significant differences from the placebo.ConclusionResveratrol is the most efficacious in relieving nasal discomfort, and cinnamon bark performs best in optimizing QoL. The results of this study provide scientific evidence for the use of botanical drugs (such as resveratrol and cinnamon) in nasal irrigation for the treatment of AR, offering new options for this disease. This is conducive to promoting the application and verification of some traditional drugs within the framework of modern medicine.Systematic Review Registrationidentifier CRD 420251054166.